Is Low-Level Visual Experience Cognitively Penetrable? - Dávid Bitter (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
Philosophers and psychologists alike have argued recently that relatively abstract beliefs or cognitive categories like those regarding race can influence the perceptual experience of relatively low-level visual features like color or lightness. Some of the proposed best empirical evidence for this claim comes from a series of experiments in which White faces were consistently judged as lighter than equiluminant Black faces, even for racially ambiguous faces that were labeled ‘White’ as opposed to ‘Black’ (Levin and Banaji 2006). The latter result is considered especially indicative of cognitive penetration, based on the reasoning that the relevant distortions were a function of lexical labeling, and hence the effect must have been mediated by categorization at the cognitive level. I argue that this reasoning is flawed, and that the assumptions on which it relies are questionable on both empirical and theoretical grounds. I propose an alternative, low-level explanation of the phenomena, which I argue is empirically more plausible and abductively preferable to the cognitive-penetration account. The upshot is that cognitively impenetrable perceptual systems may be psychologically more plastic and hence philosophically more significant than is nowadays commonly assumed.
Keywords: abstract beliefs; cognitive categories; cognitive penetration; perceptual systems